# math

posted by .

find the inverse of
f(x)=-5+log(base5)(y-5)

• math -

y = 5 + log_5(x-5)
y-5 = log_5(x-5)
5^(y-5) = x-5
x = 5 + 5^(y-5)

so, f^-1(x) = 5 + 5^(x-5)

## Similar Questions

1. ### math

Could you show me step by step how to find the inverse of this problem: log with base of 2 (x+1) Thanks! It is not clear what the problem is. You are given a function of x. Let's calli it y. Are you trying to come up with an equation …
2. ### Inverse of log function

Find the inverse of f(x) = log(2+x) - 4 the base is "a" Call f(x) y y = loga(2+x) -4 y+4 = loga(2+x) a^(y+4) = 2 + x x = a^(y+4) - 2 drwls, you have merely solved the equation for x. The question was to find the "inverse", so the actual …
3. ### Math: Algebra2 Logarithms

Can someone help me find the value of B in this expression?
4. ### Maths

I got this question, and found what I believe to be the solution, but want it confirmed. I started with: log[base5](2x+1) + log[base5](x-1) = 1 And used the product law: log[base5]((2x+1)(x-1)) = 1 log[base5](2x^2-x-1) = 1 Then I changed …
5. ### Math

log(base5)x+log(base25)x+log(base125)x=33 solve for x
6. ### mathematics

Need help with these: Write the expression as a logarithm of a single quality. a) 3log[base5](a) + 4log[base5](b) - 2log[base5](c) b) 3log(2)-(1/3)log((x)^(2) - 1) I appreciate help.